SOCIAL ATOMISATION OF A PERSONALITY IN THE PERIOD OF GLOBAL INFORMATIZATION OF THE SOCIETY - Marčenoka, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Development of information technology as a technical basis of the modern society enters all spheres of life of the society and influences significantly ways and forms of existence of every individual. On the one hand, intensive application of information technology innovations in the society’s everyday life and appearance of the sphere of virtual communication create wide space for realisation of possibilities, but on the other hand, it often leads to social atomisation of a personality. Urgency of the given research is caused by dynamics of the information flow as a global factor of contemporaneity that gave rise to the problem of social atomisation of the personality expressed in mediated communication, characterised by isolation of the individual, when the virtual environment becomes the main channel of communication excluding traditional ways of relations.